Strategi Perencanaan Peningkatan Mutu Pendidikan di Sekolah Dasar: Kajian Analisis SWOT - Kriswanto, Didi (Kayon Media, 2025)
The quality of education needs to be studied in depth and continuously to remain relevant to changes and developments in the era. This study aims to formulate a planning strategy to improve the quality of education in Elementary Schools through a SWOT analysis. This study uses a qualitative approach with a case study. The data collection techniques are interviews and observations, with research subjects determined using purposive sampling. A triangulation test of sources and techniques was carried out to test the validity of the data. The data analysis process includes data collection, data reduction, data presentation, and verification or conclusion. The results of the study indicate that alternative planning strategies to improve the quality of education in Elementary Schools, based on the SWOT analysis study, include: 1) Improving teacher competence; 2) Increasing the effectiveness of the use of facilities and infrastructure; 3) Increasing student learning motivation; and 4) Increasing the role of stakeholders